Bibliographical Commentaries on Present-Day Spanish-American Ethnomusicology. (Revista Argentina de Musicología, 2012)
This text presents a bibliographical introduction to recent Latin American ethnomusicology in the form of brief references to numerous books, articles and papers published from 2000 to the present. It is not intended to achieve completeness but to provide a guide for those who want to know some of the results of ethnomusicological research practiced in Spanish-speaking countries or produced by Hispano-American scholars anywhere in the world.
Keywords: ethnomusicology; Spanish America; bibliography